Livelihood Assets and Households Vulnerability toward Food Commodity Price: An Evidence from Post-Disaster Community in Banda Aceh - Zikri, Irfan; Hasibuan, Indiriyani; Sofyan, Sofyan; Ginting, Litna Nurjannah; Takahashi, Makoto; Hamid, Ahmad Humam (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
The recovery process following the 2004 mega-disaster and the Covid-19 pandemic have significant implications for the dynamics of change and community resilience in Banda Aceh. A resilient community is characterized by the ability to adapt to various threat risks, including volatile market conditions. Therefore, this study aimed to investigate livelihood assets in Banda Aceh and the influence on households vulnerability to fluctuation in the market price of food commodity. To achieve this objective, the study used a questionnaire survey method with 560 household heads as the unit of analysis spread across 28 villages in Banda Aceh. Furthermore, data were analyzed using a descriptive method to calculate livelihood assets and vulnerability index, along with multiple linear regression to analyze the effect of livelihood capital on vulnerability. The results showed that the condition of human and financial capital was still weak compared to social and physical capital. Households also had a high level of vulnerability to fluctuation in food prices. Statistically, human, financial, and social capital had a significant effect on households vulnerability. This study showed the importance of fostering both human and financial capital at the households level to improvequality of life and economic resilience. There were also needs for initiatives to improve social networks as a means of adapting to unexpected events.